The Effect of Green Marketing, Customer Experience and Product Qual-ity on Repurchase Intention (Study on Avoskin Skincare Product Con-sumers in Magelang) - Irawati, Anifah (Trunojoyo University of Madura, 2025)
The purpose of this study was to determine how the variables of green marketing, customer experience and product quality affect the repurchase intention variable on Avoskin skincare products in Magelang. This study uses quantitative methods with purposive sampling techniques. A total of 100 respondents were asked to fill out a questionnaire with the condition that they had purchased Avoskin products through the official shopee store at least twice. Data were collected through questionnaires and analyzed using multiple liner regression. The study results show that only green marketing variables have a positive and significant effect on repurchase intention. Meanwhile, the customer experience and product quality variables have no effect on repurchase intention. The results of this study indicate that Magelang people's awareness of environmental values reflected in Avoskin's green marketing strategies such as the use of natural ingredients and environmentally friendly packaging more influence the interest in making repeat purchases. However, unsatisfactory customer experience variables and inconsistent product quality in Avoskin products are a barrier for consumers to repurchase products. According to this study, companies must prioritize customer satisfaction and product quality consistency to maintain customer loyalty in the long term, even though green marketing strategies can attract consumers who care about the environment.